Two small RNAs encoded by Epstein-Barr virus can functionally substitute for the virus-associated RNAs in the lytic growth of adenovirus 5. - Bhat, R A (1983)
Adenovirus (Ad) serotypes 2 and 5 synthesize large amounts of two low molecular weight RNAs designated virus-associated (VA) 1 and 2. Recently, genetic and biochemical approaches have been used to show that Ad2 VA1 RNA is required for efficient translation of viral mRNAs produced at late times after infection. Primate cells harboring the Epstein-Barr virus genome (EBV) synthesize large amounts of two low molecular weight RNAs: EBER1 and EBER2. Striking similarities of gene organization have been noted between the genes coding for Ad5 VA RNAs and the EBV EBERs [Rosa, M. D., Gottlieb, E., Lerner, M. R. & Steitz, J. A. (1981) Mol. Cell. Biol. 1, 785-796]. To examine whether the EBRs can functionally substitute for the VA RNAs for the lytic growth of Ad5, we have constructed an Ad5 substitution mutant in which the two VA RNA genes have been deleted and replaced by an EBV DNA segment coding for the two EBERs. The resulting Ad5 mutant synthesizes large amounts of the EBERs and is viable. Thus, two small RNAs of EBV origin, having primary and secondary structures different from those of the VA RNAs, can functionally substitute for the VA RNAs in the lytic growth of Ad5. These results are discussed in the context of mechanism of function of the VA RNAs.